The Effect of Islamic Advertising and Brand Image on Sasha Toothpaste Product Purchase Decision - Tussifah, Hamidah; Hasni, Gina Atikah; Hasanah, Anisa Nur (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: The purpose of this study was to find out the effect of Islamic advertising and brand image on Sasha's toothpaste product purchase decision on students at the University of Darussalam Gontor Female Campus. Design/Methode/Approach: The research method used was quantitative, the sample was used by 143 respondents. Data collection techniques with questionnaire deployment and data analysis techniques use multiple linear regression analysis. Research Finding: The results of this study showed that there was a positive and significant effect between Islamic advertising and brand image variables on the purchase decision of Sasha toothpaste products. Theoretical contribution/Originality: Islamic advertising is one of the advertising offerings that are often used today. A brand image reflects a consumer's perception of a product or brand. Practitioner/Policy implication: The important role of Islamic advertising and Brand image can influence a consumer's purchase decision, therefore this must be very concerning for companies to form an image and determine target consumers. Research limitation: The limitations of this research are does not account for unexpected events like the current pandemic, this affects the limited number of respondents, so the respondents are only female students from the University of Darussalam Gontor.